2021
DOI: 10.21203/rs.3.rs-870780/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Characterization of SSR Markers in the Gossypium Barbadense Genome

Abstract: BackgroundThe fiber quality and resistance traits of Gossypium barbadense are considerably better than that of other Gossypium species. Simple sequence repeats (SSRs) are user friendly, low cost markers widely used in genetic studies. However, most SSRs have been developed from G. hirsutum, G. arboreum, and G. raimondii; no genome-wide SSRs have been developed from G. barbadense.The de novo sequences of G. barbadense cv. Xinhai21 were utilized to develop SSR markers and scanned to detect SSRs using the MIcroSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Also, the results indicated that mean performance for most selected families differed; these results could be due to gene expression for these families; therefore, selection for adaptable families and higher than means for better parent and commercial variety well be a help to produce high yielding recombination and earlier to grow it often winter cropping without a decrease in yield. These results are in harmony with those previously reported [33,[46][47][48][49][50]. It appeared that most of the yield and its component traits were positive and either significant or highly significant correlated with each other, indicating that these traits are essential components of cotton yield.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the results indicated that mean performance for most selected families differed; these results could be due to gene expression for these families; therefore, selection for adaptable families and higher than means for better parent and commercial variety well be a help to produce high yielding recombination and earlier to grow it often winter cropping without a decrease in yield. These results are in harmony with those previously reported [33,[46][47][48][49][50]. It appeared that most of the yield and its component traits were positive and either significant or highly significant correlated with each other, indicating that these traits are essential components of cotton yield.…”
Section: Discussionsupporting
confidence: 90%
“…The main objective of any breeder is to get a high yield with acceptable fiber qualities, especially under normal conditions in general 9,10,25 ., and underwater deficit stress conditions in special 3,6,36,[51][52][53] .This work suggested Table 5. Means and their percent from the better parent of the superior four families scored by using two selection procedures for studied characters in the F 4 generation.…”
Section: Discussionmentioning
confidence: 99%